If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(12 + 2X) = 39 5x + (12 * -1 + 2X * -1) = 39 5x + (-12 + -2X) = 39 Reorder the terms: -12 + -2X + 5x = 39 Solving -12 + -2X + 5x = 39 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '12' to each side of the equation. -12 + -2X + 12 + 5x = 39 + 12 Reorder the terms: -12 + 12 + -2X + 5x = 39 + 12 Combine like terms: -12 + 12 = 0 0 + -2X + 5x = 39 + 12 -2X + 5x = 39 + 12 Combine like terms: 39 + 12 = 51 -2X + 5x = 51 Add '-5x' to each side of the equation. -2X + 5x + -5x = 51 + -5x Combine like terms: 5x + -5x = 0 -2X + 0 = 51 + -5x -2X = 51 + -5x Divide each side by '-2'. X = -25.5 + 2.5x Simplifying X = -25.5 + 2.5x
| 0.02x=-18 | | 0.03x=6 | | -6(x-1)= | | 179=15-x | | 30x^3+62x^2-48x=0 | | 30=2(y+6)-5y | | 3(2-3)=5(23-7)+2 | | 7(6+2x)=140 | | 33-2-3=7-3 | | 5x-4=x+24 | | X^2+y^2-6y-247=0 | | -2x+6y=36 | | 3(x-1)=2-3+3x | | y-6=6x-11 | | X-3/x=x-4/x-2 | | 1-7x=-x-59 | | x+(545-x)=545 | | 1/2-(-1/4) | | 5(4-3x)=-145 | | (3-2)/(1-5) | | x+y=545 | | (2-3)/(5-1) | | -11-(-3)= | | 2-3/5-1 | | x+(x+2)=545 | | 4(-2x+1)=-28 | | (2/3)*x+5=(-1/3)*x+17 | | 16-32= | | 2/3x+5=-1/3x+17 | | 4(-3x+6)=168 | | 2/3x+1/2-5/6x=3/4-5/12x | | -96=-8n |